Increased Ratio of Non-mercaptalbumin-1 Among Total Plasma Albumin Demonstrates Potential Protein Undernutrition in Adult Rats - Wada, Yasuaki; Komatsu, Yosuke; Izumi, Hirohisa; Shimizu, Takashi; Takeda, Yasuhiro; Kuwahata, Masashi (Frontiers in Nutrition, 2018)
The redox state of plasma albumin shifts in response to dietary protein intake in growing rats, and the shift is more sensitive than that of plasma albumin level, a classical marker of protein nutritional status. While it has been suggested that plasma albumin redox state could be useful as a novel marker of protein nutritional status, the above animal model is highly sensitive to dietary protein intake and the observation may not be extrapolated widely to humans. This study aimed to investigate whether albumin redox state also reflects protein nutritional status in adult rats, which have a lower dietary protein requirement and are less responsive to protein intake. Male adult rats were placed on AIN-93M diet (14% casein), or AIN-93M-based low protein diets (10% or 5% casein) ad libitum for 24 weeks. Whereas there was no significant difference in body weight between the groups at the end of the experimental period, the 5% casein diet group had the smallest gastrocnemius muscle weight among the groups, which was significantly lower than that of the 10% casein diet group. Plasma albumin level was also lower in the 5% casein diet group compared with the other groups, but the differences were limited and inconsistent during the experimental period. Among the albumin redox isoforms such as mercaptalbumin, non-mercaptalbumin-1, and non-mercaptalbumin-2, the ratio of non-mercaptalbumin-1 among total albumin was significantly higher in the 5% casein diet group, and the increase remained constant throughout the experimental period. Increased non-mercaptalbumin-1 ratio would thus demonstrate the presence of potential protein undernutrition in adult rats, as manifested only by a decreased gain in a specific type of skeletal muscle; non-mercaptalbumin-1 among total albumin ratio could be useful as a robust marker of protein nutritional status.